Knowledge management system framework for collaborative open source software development - Lakulu, Modi (2012)
The global economy crisis has made software development a prohibitively expensive undertaking, thus forces developers to look for a viable alternative, namely the Open Source Software (OSS). In addition to low acquisition cost, free access to OSS source codes and components provides a more flexible, highly customizable development process. In the realm of software development, the emerging Open Source Software Development (OSSD) brings in altogether a new concept of software engineering that revolutionizes the software process and working culture. In this regard, some researchers have raised critical questions pertaining to the appropriate life-cycle that underpins an OSS model, the optimal methodology to support the OSSD, and the essential toolkits to support the OSS methodology. Currently, there is a lack of knowledge concerning a development model for Knowledge Management System (KMS), and the architecture to support a collaborative OSSD that can facilitate knowledge sharing among practitioners. Thus, the researcher undertook a study to investigate the current practice and to identify the relevant system components that lead to a sound and viable KMS framework for knowledge sharing in the OSS development. The formulation of the framework was realized through a critical review of the current and major methodologies in software development; however, the development of a system prototype, which was based on the prototype approach, only focused on the System Development Life Cycle (SDLC). A survey was conducted on selected OSS developers in Malaysia for the following purposes: to measure their awareness of OSS and KM, to elicit feedback on the proposed framework that could support a collaborative software development, and to validate the proposed framework’s components. Data gathered were analyzed using the Rasch Model and the internal reliability statistical procedure in SPSS that revealed a highly reliable instrument, which was based on Cronbach Alpha’s reliability coefficient of 0.97. The findings also indicated that an overwhelming majority of the respondents agreed that OSS tools for software development were urgently needed. They also concurred that using and managing these tools had to be carefully appraised for a particular knowledge domain,which could expedite the software development process. Overall, this study provides useful insights regarding the formulation of a viable KMS prototype underpinned soundly by theoretical and methodological judgments that fosters a collaborative software development environment. Lessons learned can also help create a new KM society that strives on the principles to work in a more supportive and responsible fashion.